ETIKA TERHADAP HEWAN: (Kajian Tafsir Ayat Sosial Terhadap Anjing Dalam Al-Qur’an) - Anggraini, Lisa; Syahidah, Lailah (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2023)
Learning Islamic law requires a thorough familiarity with the Qur’an, hence its study is crucial. One of them is the state of the art in canine poop education and sanitation. varied specialists have varied perspectives on dogs because of the variety of functions and benefits they play for people and the variety of approaches utilised to comprehend dogs. Among the jurists, Imam Shafi'i argued that this proves that canines are highly impure (mughalladzah), while Imam Malik bin Anas-Maliki held that dogs are not impure and that licking dogs is a form of worship (ta'abbud) that requires no more than seven washes. Similarly, Imam Shafi'i maintained that it is still forbidden to own a dog, although Malik bin Anas-Maliki held that doing so was permissible. Modern academics shared this view. The author primarily discusses canines from the viewpoint of the Qur'an, whose commentary takes the form of interpretations, discussing how canines are portrayed in real life and how the Qur'an explains the uniqueness of a dog.